Tp-e interval and Tp-e/QT ratio in clinically stable pediatric heart transplant recipients - Serhat Koca; Feyza Ayşenur Paç; Sabit Kocabeyoğlu; Maze Zabun; Deniz Eriş; Doğan Emre Sert; Ümit Kervan; Mustafa Paç (KARE Publishing, 2019)
Objective: A study of the T wave peak-to-end (Tp-e) interval, the Tp-e/QT ratio, and the Tp-e/QTc ratio in pediatric heart transplant recipients (HTRs), a group which has a higher risk of sudden cardiac death than the normal population, has not previously been reported. The aim of this study was to assess alterations in ventricular repolarization using the Tp-e interval, Tp-e/ QT ratio, and Tp-e/QTc ratio in clinically stable pediatric HTRs. Methods: A total of 13 clinically stable HTRs, 13 patients who had undergone cardiac surgery (CS) under cardiopulmonary bypass, and 16 healthy controls under 18 years of age were retrospectively evaluated. Results: No significant differences were observed between the HTR, CS, and control groups in terms of QTc, JTc interval, and T wave amplitude (p>0.05). The Tp-e interval (p=0.001), Tp-e/QT ratio (p<0.001), and Tp-e/QTc ratio (p=0.001) were significantly higher in the HTR group compared with the CS and normal control participants. Conclusion: The Tp-e interval, Tp-e/QT ratio, and Tp-e/QTc ratio were elevated in stable HTRs compared with the normal and CS groups.